Social and medical need for whole genome high resolution NIPT - Malgorzata I. Srebniak; Maarten F. C. M. Knapen; Lutgarde C. P. Govaerts; Marike Polak; Marieke Joosten; Karin E. M. Diderich; Laura J. C. M. van Zutven; Krista A. K. E. Prinsen; Sam Riedijk; Attie T. J. I. Go; Robert‐Jan H. Galjaard; Lies H. Hoefsloot; et al. (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Two technological innovations in the last decade significantly influenced the diagnostic yield of prenatal cytogenetic testing: genomic microarray allowing high resolution analysis and noninvasive prenatal testing (NIPT) focusing on aneuploidy. To anticipate future trends in prenatal screening and diagnosis, we evaluated the number of invasive tests in our center and the number of aberrant cases diagnosed in the last decade. Methods We retrospectively analyzed fetal chromosomal aberrations diagnosed in 2009–2018 in 8,608 pregnancies without ultrasound anomalies. Results The introduction of NIPT as the first‐tier test led to a substantial decrease in the number of invasive tests and a substantially increased diagnostic yield of aneuploidies in the first trimester. However, we have also noted a decreased detection of submicroscopic aberrations, since the number of invasive tests substantially decreased. We have observed that pregnant women were interested in broader scope of prenatal screening and diagnosis than detection of common trisomies. Conclusion Since the frequency of syndromic disorders caused by microdeletions/microduplications is substantial and current routine NIPT and ultrasound investigations are not able to detect them, we suggest that a noninvasive test with resolution comparable to microarrays should be developed, which will also meet patient's needs.